The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2355/isijinternational.47.1178
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Austenite Grain Growth in ASTM A213–T91 Steel

Abstract: Heterogeneous grain growth during austenitization in ASTM A213-T91 steel has been studied using a Gleeble 3500 thermomechanical simulator. Starting from a uniform, fine austenite grain size distribution after 1 min austenite holding time, a heterogeneous austenite grain size distribution was observed after 15 min austenite holding time at 1 060°C and 1 080°C. The state of precipitation of second phase particles was studied in detail as a function of austenitization time. The particle size distribution changed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The results correspond to the series of samples heated to austenite at a rate of 30°C s −1 , and determined that precipitates are MX type carbonitrides. Composition measurements are clearly located around Nb rich values, in agreement with previous results indicating that Nb rich phases are the only stable ones in austenite at high temperatures 34. However, even considering that the size of the particle sample taken in each case could bias the obtained results, an incipient trend is observed in Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results correspond to the series of samples heated to austenite at a rate of 30°C s −1 , and determined that precipitates are MX type carbonitrides. Composition measurements are clearly located around Nb rich values, in agreement with previous results indicating that Nb rich phases are the only stable ones in austenite at high temperatures 34. However, even considering that the size of the particle sample taken in each case could bias the obtained results, an incipient trend is observed in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Composition measurements are clearly located around Nb rich values, in agreement with previous results indicating that Nb rich phases are the only stable ones in austenite at high temperatures. 34 However, even considering that the size of the particle sample taken in each case could bias the obtained results, an incipient trend is observed in Fig. 11 that indicates a V enrichment of the precipitated phases after the complete thermal cycle when the time in the tempering step is increased.…”
Section: Dilatometric Record Of Austenitisation Processmentioning
confidence: 94%
“…These latter precipitates present smaller size than the Nb-rich ones, and they are formed at tempering temperatures of 600 °C and above. Zavaleta-Gutiérrez et al (2007) observed the type I, type II and type III MX precipitates. The type I and type II precipitates correspond respectively to the Nb-rich and the V-rich precipitates found in the present investigation.…”
Section: Conditionmentioning
confidence: 95%
“…1) However, such high-temperature carburization can cause abnormal austenite (γ ) grain growth 2) and, accordingly, degrade the fatigue performance and toughness of the steel components. The abnormal grain growth can be prevented by the addition of micro-alloying elements to form pinning particles, including AlN, 3,4) Nb(C,N), 3,[5][6][7][8][9][10][11] TiN 12) and V(C,N), 13) where TiN or a combination of AlN and Nb(C,N) are most commonly used in industrial applications.…”
Section: Introductionmentioning
confidence: 99%